Prediction of Psychosomatic Symptoms Based on Adverse Childhood Experiences and Cognitive Emotion Regulation in Individuals Aged 20 to 50 Years - Khashabizadeh, Mozhdeh; Behzadi, Safieh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study aimed to determine the relationship between adverse childhood experiences and cognitive emotion regulation with psychosomatic symptoms in adults. Methods and Materials: The research method was correlational. The statistical population consisted of all individuals aged 20 to 50 years residing in Shiraz in the year 2024. From this population, 300 individuals were selected through convenience sampling. The research instruments included the Somatization Questionnaire by Kroenke et al. (2002), the Adverse Childhood Experiences Questionnaire by Felitti et al. (1998), and the Cognitive Emotion Regulation Questionnaire by Garnefski and Kraaij (2006). Data analysis was conducted using multiple regression with SPSS software. Findings: The results indicated that there was no significant relationship between adverse childhood experiences and psychosomatic symptoms in adults. However, adaptive cognitive emotion regulation was found to predict psychosomatic symptoms with a regression slope of -0.091 in the linear equation. Moreover, maladaptive cognitive emotion regulation could predict psychosomatic symptoms with a regression slope of 0.443 in the linear equation. Conclusion: Therefore, it is concluded that adverse childhood experiences do not predict psychosomatic symptoms; however, cognitive emotion regulation can predict psychosomatic symptoms in adults.